Visualization and quantification of peat substrate moisture by fully automated moisture controlling system (SMCS) in forest container nursery - Durło, Grzegorz; Banach, Jacek; Kormanek, Mariusz; Małek, Stanisław (Leśne Prace Badawcze, 2018)
This study explores the use of fully automatic monitoring system of peat moss substrate moisture under pine seedlings at Rudy Raciborskie forest nursery in the Silesian Upland. A brand new multipoint system for this study was created. The multichannel electronic recorder MPI-DN Metronic was the main part of the project. Twelve HD3910.2 probes (three electrodes) for volumetric water content measurement were used in a distributed configuration. Modbus RTU protocols were used for data transmission and the results were archived into an internal memory. One probe delivers 1440 measurements a day. Based on the average substrate moisture data from the field, the recorder controls the watering system according to the precisely defined parameters. Proper placement of sensors in the field allows for accurate analysis of the temporal and spatial variability of peat moss substrate moisture. Results of the statistical analysis have confirmed that the peat moss moisture is significantly differentiated within the homogeneous production field of the forest seedlings. The study findings suggest that irrigation systems should be adapted to specific situation of substrate moisture at the nursery surfaces aimed at optimised water management.